IMPLEMENTASI PERDA NO. 12 TAHUN 2001 TENTANG PEMAKAIAN BUSANA MELAYU DI LINGKUNGAN PENDIDIKAN, PEGAWAI NEGERI SIPIL, SWASTA / BADAN USAHA MILIK DAERAH DI KANTOR DINAS PENDAPATAN DAERAH KOTA PEKANBARU TAHUN 2014 - Jonita, Cori; Asrida, Wan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
All associated with social norms, religion, customs, so clothing developed with the meaning of varied. Riau especially the City of Pekanbaru, ranging from the building to the street name indentik with malay, especially government buildings and museum. Malay clothes must be used by all levels of the start of the level of education from kindergarten to Senior High School private and state that is clothed in the Malays that the model is determined by the school and used on Friday. Malay clothes using some unique motifs malay, until the Malay batik. The purpose of this research is to know the implementation of Perda No. 12 2001 at the office of Regional Income City of Pekanbaru.Research method that will be used is a research survey. The location of this research is in the office of Regional Income City of Pekanbaru located in the way the Lotus, because they see government officials have not maximum of implementing Perda No. 12 The year 2001 about malay fashion consumption in the educational environment, Civil Servants, Private/Enterprises area. The reason for the taking of research in this location is because there is no scientific research reveals the problem as noted in this research.The results of research on the implementation of the Perda No. 12 2001 at the office of Regional Income City of Pekanbaru Years 2014, including the category of good, this shows that the policy of Malay fashion consumption in the City of Pekanbaru still needs to be repaired and improved again. Should the leaders of increasing positive influence to the officials with how to give an example of an example or a good example, has authority in front of civil servants in order to grow their sense of withheld or respect.Key Words : Implementation, Perda No. 12 2001, of Regional Income City of Pekanbaru.